1999
DOI: 10.1046/j.1523-1755.1999.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased NAD(P)H oxidase-mediated superoxide production in renovascular hypertension: Evidence for an involvement of protein kinase C

Abstract: We therefore conclude that renovascular hypertension in 2K-1C rats is associated with increased vascular O-.2 leading to impaired vasodilator responses to endogenous and exogenous nitrovasodilators. Increased vascular O-.2 is likely secondary to a PKC-mediated activation of a membrane-associated NAD(P)H-dependent oxidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
180
4
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 28 publications
7
180
4
5
Order By: Relevance
“…4 Therefore, we elected to study the relation between oxidative stress and oxygenation more directly in the present series in a model of extreme Ang II action in the clipped kidney of 2K,1C rats. Previous studies in the 2K,1C pig 15 and rat 16 showed that increased oxidative stress was associated with high renin levels in the early phase. We have consistently observed low pO 2 in the cortex of hypertensive kidneys, which also demonstrate high oxidative stress and deficient NO.…”
Section: Discussionmentioning
confidence: 87%
“…4 Therefore, we elected to study the relation between oxidative stress and oxygenation more directly in the present series in a model of extreme Ang II action in the clipped kidney of 2K,1C rats. Previous studies in the 2K,1C pig 15 and rat 16 showed that increased oxidative stress was associated with high renin levels in the early phase. We have consistently observed low pO 2 in the cortex of hypertensive kidneys, which also demonstrate high oxidative stress and deficient NO.…”
Section: Discussionmentioning
confidence: 87%
“…In line with this, it has been suggested that protein kinase C activity, which is involved in NADPH oxidase activation, is increased constitutively in renovascular hypertension. 21 Moreover, increased wall stretch, angiotensin II, and hypertension per se are known to increase protein kinase C activity. [22][23][24][25] Without a doubt, the impact of renovascular hypertension on endothelium-dependent relaxation was small in the present study compared with previous observations in humans 11 and rats.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Without a doubt, the impact of renovascular hypertension on endothelium-dependent relaxation was small in the present study compared with previous observations in humans 11 and rats. 21 However, it is well known that mice are less susceptible to endothelial dysfunction than, for example, rats. The aorta of mice contains large amounts of extracellular SOD, attenuating the impact of oxidative stress on NO bioavailability, 26 a fact that might also explain the relatively mild increase in vascular O 2 Ϫ formation after clipping of WT animals.…”
Section: Discussionmentioning
confidence: 99%
“…62 The effects of endothelin-1 include direct vasoconstriction, a positive feedback increase of angiotensin II production, and the activation of protein kinase C (PKC). 61 In turn, PKC stimulates a NAD(P)H oxidase-mediated ·O 2 Ϫ production 63 and might be autocatalytically activated by ·O 2 Ϫ . 64 In addition, PKC-mediated phosphorylation causes inhibition of NOS, 65 and a recent report demonstrated that angiotensin II, via an ·O 2 Ϫ -and PKC-mediated mechanism, can trigger NOS uncoupling.…”
Section: Neurohormonal Activation and The Control Of ·O 2 ؊ Productionmentioning
confidence: 99%